To add two numbers in scientific notation, they must first have the same exponent. Let's choose \(3.2 \times 10^4\) and \(1.95 \times 10^6\).
Step 1: Adjust the numbers to have the same exponent
We can convert \(3.2 \times 10^4\) to have the same exponent as \(1.95 \times 10^6\). Since \(10^6\) is larger than \(10^4\), we will convert \(3.2 \times 10^4\) to \(10^6\):
\[ 3.2 \times 10^4 = 3.2 \times 10^4 \cdot \frac{10^2}{10^2} = 3.2 \times 100 \times 10^{-2} = 320 \times 10^{-2} \]
So, we rewrite \(3.2 \times 10^4\) as:
\[ 320 \times 10^{-2} \]
Step 2: Make the addition
Now we can add \(320 \times 10^{-2}\) and \(1.95 \times 10^6\) after converting \(1.95 \times 10^6\) to match the exponent:
\[ 1.95 \times 10^6 = 1.95 \times 10^6 \cdot \frac{10^{-4}}{10^{-4}} = 1.95 \times 10^2 \times 10^4 = 195000 \times 10^{-4} \]
Convert \(320 \times 10^{-2}\) into \(10^{-4}\):
\[ 320 \times 10^{-2} = 320 \times 10^{2} \cdot 10^{-4} = 32000 \times 10^{-4} \]
Step 3: Add the two numbers
Now we can add:
\[ 32000 \times 10^{-4} + 1950000 \times 10^{-4} = (32000 + 1950000) \times 10^{-4} = 1982000 \times 10^{-4} \]
Step 4: Convert back to scientific notation
Now we convert \(1982000 \times 10^{-4}\) back to scientific notation:
\[ 1982000 = 1.982 \times 10^6 \]
So,
\[ 1982000 \times 10^{-4} = 1.982 \times 10^{2} \]
Final Result
Thus, the sum of \(3.2 \times 10^4\) and \(1.95 \times 10^6\) is:
\[ 1.982 \times 10^{2} \]